Study of the thermo-hydraulic behavior of an air-PCM exchanger - RAHMOUNE AHMED; KHALED ABDERAHMANE; BELLAHCENE Lahcene (Amar Telidji- Laghouat University FACULTY OF TECHNOLOGY. MECHANICAL ENGINEERING DEPARTMENT, 2025)
This numerical investigation aims to study the storage of solar energy in horizontal heat exchanger pipe using phase change material (PCM). Focusing on its thermal performance, fluid dynamics, and energy storage efficiency. PCMs are widely used in thermal management systems due to their high energy storage density during phase transitions, making them ideal for applications such as HVAC systems, renewable energy storage, and electronic cooling. However, the interaction between air (as the heat transfer fluid) and PCM within the exchanger presents complex thermo-hydraulic challenges, including variable thermal resistance, transient heat transfer, and airflow distribution effects. The technique of heat transfer enhancement is used to understand the melting and solidification process phenomenon in a horizontal coaxial heat pipe type latent thermal energy storage (LHTES) unit. the enthalpy porosity method is used to solve the process of solidification and melting phenomenon of PCMs, using CFD code (computation fluid dynamics). The parameters studied are temperature distribution and liquid fraction to describe the charge/discharge process in the heat pipe. The computational results showed that PCM can increase the imposed temperature with ΔT max =19°𝐶 and ΔT min =6°𝐶 , and the outer air temperature fluctuated between 38°𝐶 - 31°𝐶 .
OPTION: ENERGETIC